2013
DOI: 10.3389/fendo.2013.00082
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of circadian genes expressed in the uterus endometrial stromal cells of pregnant rats as revealed by DNA microarray coupled with RNA interference

Abstract: The peripheral circadian oscillator plays an essential role in synchronizing local physiology to operate in a circadian manner via regulation of the expression of clock-controlled genes. The present study aimed to evaluate the circadian rhythms of clock genes and clock-controlled genes expressed in the rat uterus endometrial stromal cells (UESCs) during the stage of implantation by a DNA microarray. Of 12,252 genes showing significantly expression, 7,235 genes displayed significant alterations. As revealed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…Moreover, our previous data obtained from a DNA microarray in UESCs isolated from day 4.5 of rat pregnancy (49) suggested that the expression level of the Ptgs2 transcript is rhythmic. In the present study, Ptgs2 expressions were affected by Bmal1-siRNA (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, our previous data obtained from a DNA microarray in UESCs isolated from day 4.5 of rat pregnancy (49) suggested that the expression level of the Ptgs2 transcript is rhythmic. In the present study, Ptgs2 expressions were affected by Bmal1-siRNA (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, aging Per1 m/m /Per2 m/m double mutation mice have a significantly reduced number of ovarian follicles, displaying a decrease in female fertility starting approximately at 20 weeks and have significantly fewer pups born from 32 weeks old and onwards [77]. The Per2 oscillation was increased in uteri endometrial stromal cells (UESCs) during implantation, and decreased during differentiation [78]. Cellular differentiation interferes with the circadian clockwork in differentiating cells.…”
Section: Per1 1 2 Andmentioning
confidence: 99%
“…To gain insight into the cellular clocks of UESCs and the circadian regulation of physiology, the global expression of the Bmp genes, which are vital for decidualized uterus function, were analyzed by DNA microarray (58). The results are shown in Fig.…”
Section: Expression Levels Of the Bmp Genes In Uescs And Whole Uterusmentioning
confidence: 99%